2016
DOI: 10.1097/iae.0000000000000866
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Infants With Retinopathy of Prematurity

Abstract: The subfoveal choroid in premature infants can be effectively evaluated using a portable SD-OCT device. Choroidal thickness gets thinner with the severity of ROP and the decrease is more prominent at the central and temporal location. Cystoid macular edema is not correlated with choroidal thickness in premature infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 26 publications
3
47
0
Order By: Relevance
“…This observation was corroborated by several independent clinical investigations, 10e12,46 wherein choroidal thinning was reported in children and adolescents Photoreceptor functional degeneration in oxygeninduced retinopathy (OIR) rats. AeQ: Scotopic electroretinogram analysis of animals at different ages (P30, P60, P150, and P210) and exposed to cycling oxygen (OIR) or maintained in normoxia (Nor) and treated or not with IL-1ra (from P1 until P14).…”
supporting
confidence: 73%
“…This observation was corroborated by several independent clinical investigations, 10e12,46 wherein choroidal thinning was reported in children and adolescents Photoreceptor functional degeneration in oxygeninduced retinopathy (OIR) rats. AeQ: Scotopic electroretinogram analysis of animals at different ages (P30, P60, P150, and P210) and exposed to cycling oxygen (OIR) or maintained in normoxia (Nor) and treated or not with IL-1ra (from P1 until P14).…”
supporting
confidence: 73%
“…In subjects with ROP, both at preterm ages (Erol et al, 2016) and in adolescence (Anderson et al, 2014), the choroid is too thin. These human data do not give temporal priority to the choroidal abnormality over the onset of ROP.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Moreno et al [35] demonstrated the feasibility of using SD-OCT to examine the choroid in premature infants, and visualized the choroidoscleral junction in 78%. Similarly, Erol et al [8] were able to measure subfoveal CT in 80% of the premature infants. The SS-OCT single scans in our study visualized the choroidoscleral junction at all eccentricities of the scan of every child and young adult, in agreement with the results reported by Copete et al [14] for healthy subjects.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies already measured CT in premature children using SD-OCT [7, 8, 10]. However, to our knowledge, this is the first study to measure CT in young preterm infants using the superior SS-OCT technique.…”
Section: Discussionmentioning
confidence: 99%